2009
DOI: 10.1890/08-0972.1
|View full text |Cite
|
Sign up to set email alerts
|

Carrion decomposition and nutrient cycling in a semiarid shrub–steppe ecosystem

Abstract: Vertebrate carrion decomposition and nutrient cycling have both direct and indirect effects on the soil properties, fauna, and flora associated with an animal's carcass. While few comprehensive quantitative studies have been undertaken, those that have show considerable variability in decomposition processes and rates, their regulating variables, and the resultant ecosystem effects. In this two-part study, decomposition rates of vertebrate species were measured in a semiarid, shrub-steppe environment (Wyoming,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
207
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(226 citation statements)
references
References 73 publications
9
207
0
Order By: Relevance
“…Similar observations have been reported that insect outbreaks reduce NEP during outbreaks but increase NEP in the year after the outbreaks (Mattson and Addy 1975;Cook et al 2008;Albani et al 2010;Amiro et al 2010). The enhanced plant productivity after outbreaks in both grassland and forest ecosystems (Risley and Crossley 1993;Towne 2000;Parmenter and MacMahon 2009) could be primarily attributable to the enhanced decomposition of plant and insect litter and subsequent increase in soil N availability. Moreover, the stimulations in 2011 compensated for the reductions in 2010 under the experimental locust outbreaks, resulting in neutral change in NEE within the 2-year experimental period.…”
Section: Discussionsupporting
confidence: 81%
“…Similar observations have been reported that insect outbreaks reduce NEP during outbreaks but increase NEP in the year after the outbreaks (Mattson and Addy 1975;Cook et al 2008;Albani et al 2010;Amiro et al 2010). The enhanced plant productivity after outbreaks in both grassland and forest ecosystems (Risley and Crossley 1993;Towne 2000;Parmenter and MacMahon 2009) could be primarily attributable to the enhanced decomposition of plant and insect litter and subsequent increase in soil N availability. Moreover, the stimulations in 2011 compensated for the reductions in 2010 under the experimental locust outbreaks, resulting in neutral change in NEE within the 2-year experimental period.…”
Section: Discussionsupporting
confidence: 81%
“…We demonstrated that delayed insect access altered subsequent insect community assembly and was associated with a slower decomposition process. Changes in decomposition is known to modify the rate of nutrient transformation and availability in the local habitat, and overall effect the ecosystem function of removing decomposing organic matter from a terrestrial habitat (Parmenter and MacMahon 2009, Hawlena et al 2012, Woodward et al 2012). Reducing the quantity or rate of nutrient reintroduction into the environment could ultimately impact other members of the community that respond to nutrient pulses (Post and Kwon 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Resource pulses such as carrion are defined as infrequent, short-lived resources that can have large impacts on ecosystem processes (Yang et al 2008). For instance, carrion nutrient transfer between ecosystems can result from blow fly (Diptera: Calliphoridae) consumption and dispersal (Hocking and Reimchen 2006, Hocking et al 2009, Parmenter and MacMahon 2009 or vertebrate scavenging (Wilson andWolkovich 2011, Beasley et al 2012). Necrophagous arthropod attraction, colonization, development, and migration can affect nutrient transformation and release and thus local biodiversity (Hocking and Reimchen 2006, Lisi and Schindler 2011, Tomberlin et al 2011, Hawlena et al 2012, which can ultimately impact landscape biodiversity depending on the density and frequency of carrion (Yang et al 2008, Barton et al 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, large amounts of keratin likely accumulate in bird colonies (Sugiura and Ikeda 2014). Although the decomposition process of vertebrate carcasses has been frequently investigated (Carter et al 2007;Parmenter and MacMahon 2009;Mondor et al 2012;Pechal et al 2014), very few studies have focused on the decomposition of keratin materials such as feathers under field conditions (Sugiura and Ikeda 2014). Keratin is one of the most abundant and highly stable animal proteins on earth (Sharma and Rajak 2003).…”
mentioning
confidence: 99%